The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of ICC/SUPERCOMM '96 - International Conference on Communications
DOI: 10.1109/icc.1996.540253
|View full text |Cite
|
Sign up to set email alerts
|

Improved decoding with the SOVA in a parallel concatenated (Turbo-code) scheme

Abstract: In this paper we will show that the soft output of the soft-outputViterbi-decoder (SOVA) suffers from two distortions: Firstly, for bad channels the reliability information of the decoder output is too optimistic. The output can be considered as being multiplied by a factor, that depends on the current bit-error-rate (BER). To become closer to the true log-likelihood ratio the output has to be normalized. Secondly, the soft-output of the SOVA -when used in Turbo decoding -is effected by a correlation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 5 publications
2
33
0
Order By: Relevance
“…Based on the remarks in [41], it is logical to define the extrinsic information as the difference between the generated soft-output value and the coherent term present in , related to the same information symbol, according to (23) We now comment on the role of switch S in Fig. 2.…”
Section: A Parallel Concatenated Codesmentioning
confidence: 99%
“…Based on the remarks in [41], it is logical to define the extrinsic information as the difference between the generated soft-output value and the coherent term present in , related to the same information symbol, according to (23) We now comment on the role of switch S in Fig. 2.…”
Section: A Parallel Concatenated Codesmentioning
confidence: 99%
“…This represents a highly wasteful system and would not be practical. It has been suggested that the high correlation between the a priori information and the extrinsic information of a module even in a turbo system can cause the performance degradation [22], [23]. In this section, we show a proper way to construct the a priori information for the main equalizer based on the extrinsic information generated by the branch equalizers when their outputs are correlated with the main equalizer output.…”
Section: Self-iterating Soft Equalizer Algorithmmentioning
confidence: 99%
“…It has been proposed to scale the extrinsic information exchanged between the constituent decoders [7][8][9]. With this modification equation (11) for branch metric calculations can be rewritten as…”
Section: Extrinsic Information Scalingmentioning
confidence: 99%
“…Extrinsic information scaling has been proposed to compensate for the optimistic LLR calculations of SOVA [9]. A gain of 0.4 dB has been reported for a code of memory length 4 at BER of 10 -4 [9]. Scaling factor modification has also been applied and tested on the MaxLog-MAP algorithm.…”
Section: Extrinsic Information Scalingmentioning
confidence: 99%